How the future works : leading flexible teams to do the best work of their lives - Elliott, Brian (Executive); Subramanian, Sheela; Kupp, Helen (Wiley, 2022)
"The pace of change in the way that we work is accelerating faster than what leaders ever imagined possible. What felt like radical shifts driven by the pandemic ended up being the beginning of empowering individuals to do their best work while also leading better lives. But achieving true flexibility -- not only in where but critically when people work -- requires overcoming decades of reflexes leaders have built up around "the right way to work" based on 9-to-5 days full of meetings in office buildings. And it requires building new reflexes, new skills, new strengths -- moving from resistance to re-design -- to lead with purpose, to coach rather than tell, and to believe that by letting go, you'll get more back. This is a how to-book that empowers leaders with the tools and tips to do better for their people and, in turn, their businesses. The insights draw from extensive original global research from Future Forum and case studies from a wide range of companies like Levi's, Genentech, Salesforce, Slack, Royal Bank of Canada, and IBM, "--